Faktor-Faktor Yang Mempengaruhi Pembelian Produk Garam Dan Air Mineral Bermerek Di Jakarta - Randy Ramadhiansa (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The addition of salt products and branded mineral water in Jakarta, a way to increase the purchase of a product is needed. he study was conducted with the aim of understanding the brand awareness of consumers and analyzing the attitude of consumers towards selected branded commodity food products. An attempt was made to examine the items influencing the purchase of selected branded commodity food products. The product chosen in this research is salt and mineral water branded in Jakarta. Sample taken from 200 respondents residing in Jakarta area of various age, gender, last education, and work. Results show visible packaging, people around, bazaars, people around, and advertising is the most important source of awareness of branded salts. availability of nutritional information, references from friends and relatives, easy availability, and price as the most important factor in purchasing branded salt and branded water. free from adulterants, free from insecticides / pesticides / harmful chemicals and social status as the most important parameters of branded salt and branded mineral water.There is a significant perception difference regarding the importance of the various factors and parameters that influence the purchase of branded and branded branded mineral water amongst respondents by demographics. This paper offers insights and information for salt and mineral water producers in Jakarta in order to address the key factors that affect consumer purchases.